FORMULATION AND IMPLEMENTATION OF MATHEMATICAL MODELS SUITABLE FOR DEFORMATION ANALYSIS OF STRUCTURES (Nigerian Journal of Technology, 2018)
Deformation monitoring is the systematic measurement and tracking of the alteration in the shape or dimensions of an object as a result of stresses induced by applied loads. Deformation monitoring is a major component of logging measured values that may be used for further computation, deformation analysis, predictive maintenance and alarming. The main purpose of structural deformation monitoring scheme and analysis is to detect any significant movements of the structure. An effective approach is to model the structure by using well-chosen discrete points located on the surface of the structure which, when situated correctly, accurately depict the characteristics of the structure. The problem of Engineering Geodesy is the formulation of the Mathematical model that will reveal the characteristic of the structure being monitored.  In this paper, the mathematical model that reveals the changes in shape of a circular reservoir structure is formulated and applied numerically. A numerical solution was carried out using the Mathematical model formulated.http://dx.doi.org/10.4314/njt.v37i2.2